O discurso institucional da/sobre a escola : uma análise da autoria e das relações de contradição - Poletto, Rosane Zordan (2007)
The proposal of this work consists of an analysis of the speeches that are found at Pedagogical Political Projects of municipal and state schools in São José do Ouro, RS. We did an analyses about the presence or absence of the authorship function and, besides the contradictions and the silence to understand the connection between those discursive mechanisms and the production of meaning. We choose speeches from 1997 to 2006 to do the analysis and it was necessary to take care about the changes that could have happened in the projects due to the educational manager changes. Taking into consideration the objectives of this work, this dissertation was divided into three chapters. The first one specifies the theoretical positions that had been adopted through the presuppositions that base the language concept. We principally wrote about the Speech Analysis theory concepts from French line (AD), that represent the theoretical line of our work such as: a basic grasp of subject, discursive formation, pedagogical speech, interspeech, discursive memory and the silence notion. The second one specifies brief considerations about the history of education in Brazil from Jesuit education to nowadays. We considered the speeches from different historic context evidencing their ideological conditions of productions. The third chapter contains the analysis of discursive sequences present in the pedagogical speeches considering the society, school, students and teachers conceptions. From determined linguistic marks, it was observed the effects of meaning produced by the silence, the authorship and the contradiction relations. The analysis showed us the absence of authorship effect in those speeches, as well as they state the authoritarian characteristic of the pedagogical speech that produce the meaning crystallization and the ideology of dominant class